El control interno y la prevención de fraudes financieros en la empresa "Dou" año 2023. - Jaramillo Toledo, Nathaly Mercedes; Asanza Olmedo, Maria Alejandra (Machala : Universidad Técnica de Machala, 2024)
The research titled "Internal control and prevention of financial fraud in the DOU company, year 2023" analyzes the effectiveness of the internal control system in the detection and prevention of financial fraud. The main objective is to measure the effectiveness of said system in the company, highlighting the evaluation of its implementation and the lack of staff training as key factors. A quantitative approach was adopted under the positivist paradigm, using the deductive method and a non-experimental cross-sectional design. The research was analytical, which made it possible to study specific data collected through closed surveys addressed to the manager, accountant and accounting assistant. The structured questionnaire facilitated the collection of key data on the internal control situation in the organization. The results indicate that the company has a formal code of ethics, but lacks specific procedures to mitigate fraud and does not carry out regular internal audits. Likewise, a lack of constant training for staff on fraud prevention and detection was identified. These deficiencies reflect limited preventive management and high vulnerability to financial risks. It is concluded that it is essential to reinforce the internal control system through clear procedures, continuous training and periodic audits, in order to reduce the risks of fraud and strengthen the financial stability of the company.
La investigación titulada "El control interno y la prevención de fraudes financieros en la empresa DOU, año 2023" analiza la efectividad del sistema de control interno en la detección y prevención de fraudes financieros. El objetivo principal es medir la efectividad de dicho sistema en la empresa, destacando la evaluación de su implementación y la falta de capacitación del personal como factores clave. Se adoptó un enfoque cuantitativo bajo el paradigma positivista, utilizando el método deductivo y un diseño no experimental de tipo transversal. La investigación fue analítica, lo que permitió estudiar datos específicos recopilados mediante encuestas cerradas dirigidas al gerente, contador y auxiliar contable. El cuestionario estructurado facilitó la recolección de datos clave sobre la situación del control interno en la organización. Los resultados indican que la empresa cuenta con un código de ética formal, pero carece de procedimientos específicos para mitigar fraudes y no realiza auditorías internas regulares. Asimismo, se identificó una falta de capacitación constante para el personal sobre prevención y detección de fraudes. Estas deficiencias reflejan una gestión preventiva limitada y una alta vulnerabilidad ante riesgos financieros. Se concluye que es fundamental reforzar el sistema de control interno mediante procedimientos claros, capacitación continua y auditorías periódicas, con el fin de reducir los riesgos de fraude y fortalecer la estabilidad financiera de la empresa.
Keywords: CONTROL INTERNO; FRAUDE FINANCIERO; PREVENCIÓN; AUDITORIA